Dartseq SNP genotypes used in the development of a cost-effective pedigree assignment tool for rohu - Hamilton, Matthew (2023)
Dartseq single nucleotide polymorphism (SNP) discrete genotype calls for WorldFish rohu genetic improvement program generation three (G3) individuals, pools and their parents. These data were generated to develop a cost-effective pedigree assignment tool for WorldFish rohu.